The Effect of Indirect Corrective Feedback Strategy on Students’ Writing Skills of Recounting Text - Arifah, Himmatul; Muhammad Edy Thoyib (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research focuses on the effectiveness of using an indirect corrective feedback strategy on students’ writing skills of recount text to provide an alternative and effective way to complete their work in writing, especially in writing recount text. The researcher uses a quasi-experimental design by Collecting data using a test, and each class is given a pre-test before treatment and a post-test after treatment. It indicates that the treatment was successful. Independent T-test calculation researcher. T-test was calculated to compare the two means between the experimental and control groups. The table above shows that the value of sig (2-tailed) is 0.000 at the critical value for the 5% level. The significance value is less than 5% or (0.000 <0.05). So, the null hypothesis can be rejected. It can be concluded that the study’s indirect corrective feedback strategy is effective